Biochemical and Nutritional Evaluation of Chlorella and Auxenochlorella Biomasses Relevant for Food Application - Canelli, Greta; Tarnutzer, Carmen; Carpine, Roberta; Neutsch, Lukas; Bolten, Christoph J.; Dionisi, Fabiola; Mathys, Alexander (Frontiers in Nutrition, 2020)
Microalgae are a source of potentially healthy and sustainable nutrients. However, the bioaccessibility of these nutrients remains uncertain. In this study, we analyzed the biomass composition of five commercial Chlorella and Auxenochlorella strains, and Chlorella vulgaris heterotrophically cultivated in our laboratory. Protein accounted for 65% ± 3% (w w-1) dry matter (DM) in all biomasses, except for the lab-grown C. vulgaris that contained 20% (w w-1) DM protein. The lipid content was comparable and ranged between 7%–10% (w w-1) DM. Most of the biomasses had a ω6-polyunsaturated fatty acids (PUFAs)/ω3-PUFAs ratio < 4, as recommended by nutritional experts. A recently published harmonized protocol for in vitro digestion was used to evaluate lipid and protein bioaccessibility. Protein bioaccessibility ranged between 60%–74% for commercial Chlorella and Auxenochlorella biomasses and was 43% for the lab-grown C. vulgaris. Lipid bioaccessibility was < 7% in commercial biomasses and 19% in the lab-grown C. vulgaris. Taken together, the results show that microalgae are promising sources of bioaccessible protein. The limited lipid bioaccessibility indicates the need for alternative upstream and downstream production strategies.